Storytelling and Narrative Legacy: Violence and the Moral Decline of Jaime Deza in Javier Marías’s Tu rostro mañana - Greenhalgh, Matthew C. (Revista Canadiense de Estudios Hispánicos, 2023)
Javier Marías combined historiography and fiction to examine the consequences of violence in Tu rostro mañana, published in three volumes: Fiebre y lanza (2002), Baile y sueño (2004), and Veneno y sombra y adiós (2007). This interpretation examines the moral decline of Jaime Deza, the narrator-protagonist, in what he sees and the stories he hears to contextualize how Marías combined history with fiction to present nuanced representations of violence. Marías envisioned violence through Deza, who searches for a usable past to navigate the dilemmas he faces in the present.